JURIDICAL ANALYSIS OF THE ALLEGED CRIMINAL OFFENSE TO MANUFACTURE A NOTARY DEED - Subiyanto Subiyanto; Gunarto Gunarto; Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Occurred facts civil law that is the buying and selling transaction with the object of property rights of the land, it resulting the appearance of absolute ownership transition. The Constitution No. 5 of 1960, the main points of Agrarian Article 20 (2), the property rights can be switch and to be redirected to another part1. That agreement of buy and sellhave been bornin seconds the reached of “agreed” regarding goods and prices2. Because it happened switch over of rights that is the absolute property rights according to the Civil Law its happened a legal relationship. So that buy and sell legitimately according to the Civil Law it can be poured into the authentic deed that made in front of the Notary public that is the deed of “the keel agreement treaty of buying and selling with the authority”. Buying and selling of the land rights be poured into the authentic deeds that made in front of the Notary public on his authority  according to the constitution, and the Notary is not a part, at the instance of the parts to poured into the authentic deed and further more it’s the lifelong responsibility notary and the notary have the principle of formal correctness so it does not have responsibility to the contents of the deed, but then is in dispute against the bad tagged, The deed has been made Notary made basic a legal disputes in volving notary that made, anytime notary can be assign as a suspect/be detained which had no connection with the contents of the deed.